Profil Terapi dan Evaluasi Peresepan Pasien Covid-19 Rawat Jalan Di RS Wafa Husada Malang: Therapy Profile and Prescription Evaluation for Covid-19 Out Patients at Wafa Husada Hospital Malang - Ilmi , Tsamrotul; Probosiwi , Neni; Sukmawati, Datin An Nisa; Nurkamah, Siti; Lestari, Sri; Tandela, Tantik (Universitas Kadiri, 2025)
Treatment of COVID-19 patients is differentiated based on the degree of symptoms. The purpose of this study was to determine the therapeutic profile and appropriateness of prescriptions for outpatient COVID-19 at Wava Husada Hospital for the period January–July 202, based on the COVID-19 Management Protocol Book, Edition 2, 2021 and the Hospital Formulary. The research method was a retrospective descriptive observational study with a purposive sampling technique. The research instruments were medical records from SIMRS and patient prescriptions. The results showed that most patients were male (53%), aged 18-44 years (60%). The treatment profile of COVID-19 patients with asymptomatic and mild symptoms, according to therapeutic class, were vitamins (40.3%), cough and cold (12.7%), antipyretic analgesics (9.1%), supplements (8.2%), and macrolide antibiotics (7.6%). The most common types of drugs were vitamin C 500 mg non-acidic (11.8%), vitamin E 400 IU (9.8%) and vitamin D 5000 IU (8.1%). The prescription compliance is 92% of drugs according to the COVID-19 Management Protocol Book Ed. 2 of 2021 and the rationality compliance is 79%. The prescription compliance according to the Hospital Formulary has been fulfilled 100%.